Political role models, child marriage, and women's autonomy over marriage in India - Carolina Castilla (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Drawing data from the India Human Development Survey 2011 and the year of the first election with reserved seats for women pradhans, I estimate the effect of the Panchayati Raj institutions on age and autonomy over marriage. Results indicate that women in local government decrease the likelihood of child marriage, and increase the age at first marriage and gauna. The effects seem to be driven by changes in gender and cultural norms, because there is a reduction in the prevalence of arranged marriages with minimum involvement of the bride. Overall results suggest a change in gender norms after 18 years of the implementation of reserved seats for women in local government.
Keywords: J12; J16; O12; 330; gender quotas; age at marriage; gender norms